THE INFLUENCE OF HUMAN RESOURCES COMPETENCY, BUDGETING POLITICS AND PROCUREMENT OF GOODS AND SERVICES ON BUDGET ABSORPTION BY BUDGET IMPLEMENTATION AS A MODERATING VARIABLE IN THE GOVERNMENT OF RIAU ISLANDS - Imelda, Imelda; Fachrudin, Fachrudin; Satriawan, Bambang; Wibisono, Chablullah; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to analyze the influence of human resource competence, budget politics, procurement of goods and services on budget absorption and to test and analyze budget implementation in moderating the relationship between human resource competence, budget politics, procurement of goods and services on budget absorption. This research uses a quantitative approach. The type of data used in this study is primary data. This research was conducted using a survey method by distributing questionnaires to regional financial managers in the Riau Islands Provincial Government. The population of this study is the financial manager of 43 Regional Apparatus Organizations as many as 115 people. Determination of the sample through saturated samples (census). The data is processed using the SEM-PLS application version 3.0. The results of this study show that budget politics, procurement of goods and services and budget implementation affect budget absorption. But on the contrary, the competence of human resources does not affect the absorption of the budget. The interaction of budget implementation can strengthen the relationship between the competence of Human Resources and the procurement of goods and services for budget absorption but is not significant in moderating the political process of budgeting for budget absorption.